Prestige and content biases together shape the cultural transmission of narratives. (29th July 2021) - Berl, Richard E.W.; Samarasinghe, Alarna N.; Roberts, Seán G.; Jordan, Fiona M.; Gavin, Michael C.
Abstract: Abstract: Cultural transmission biases such as prestige are thought to have been a primary driver in shaping the dynamics of human cultural evolution. However, few empirical studies have measured the importance of prestige relative to other effects, such as content biases present within the information being transmitted. Here, we report the findings of an experimental transmission study designed to compare the simultaneous effects of a model using a high- or low-prestige regional accent with the presence of narrative content containing social, survival, emotional, moral, rational, or counterintuitive information in the form of a creation story. Results from multimodel inference reveal that prestige is a significant factor in determining the salience and recall of information, but that several content biases, specifically social, survival, negative emotional, and biological counterintuitive information, are significantly more influential. Further, we find evidence that reliance on prestige cues may serve as a conditional learning strategy when no content cues are available. Our results demonstrate that content biases serve a vital and underappreciated role in cultural transmission and cultural evolution. Social media summary: Storyteller and tale are both key to memorability, but some content is more important than the storyteller's prestige.